Final answer:
To determine the values of the constant r for which y = e^rx is a solution of the given differential equation, we substitute y = e^rx into the equation and solve for r. The values of r that make y = e^rx a solution are approximately (-3 + √57)/6 and (-3 - √57)/6.
Step-by-step explanation:
To determine the values of the constant r for which the function y = e^rx is a solution of the given second order linear differential equation 3y''+3y'-4y=0, we substitute y = e^rx into the equation and solve for r.
Substituting y = e^rx into the equation, we obtain:
3(e^rx)'' + 3(e^rx)' - 4(e^rx) = 0
Simplifying and rearranging the equation, we get:
3r^2e^rx + 3re^rx - 4e^rx = 0
Factoring out the common factor e^rx, we have:
(3r^2 + 3r - 4)e^rx = 0
For the equation to hold true for all values of x, the coefficient of e^rx must be equal to zero.
Therefore, we solve the quadratic equation 3r^2 + 3r - 4 = 0 to find the values of r that make y = e^rx a solution.
Using the quadratic formula, we have:
r = (-3 ± √(3^2 - 4(3)(-4))) / (2(3))
Simplifying further, we get:
r = (-3 ± √(9 + 48)) / 6
r = (-3 ± √57) / 6
So, the values of r for which y = e^rx is a solution of the equation are approximately:
r ≈ (-3 + √57) / 6
r ≈ (-3 - √57) / 6